Development and usability testing of HEARTPA♀N: protocol for a mixed methods strategy to develop an integrated smartphone and web-based intervention for women with cardiac pain. Issue 3 (9th March 2020) - Parry, Monica; Dhukai, Abida; Clarke, Hance; Bjørnnes, Ann Kristin; Cafazzo, Joseph A; Cooper, Lynn; Harvey, Paula; Katz, Joel; Lalloo, Chitra; Leegaard, Marit; Légaré, France; Lovas, Mike; et al.
Abstract : Introduction: More women experience cardiac pain related to coronary artery disease and cardiac procedures compared with men. The overall goal of this programme of research is to develop an integrated smartphone and web-based intervention (HEARTPA♀N) to help women recognise and self-manage cardiac pain. Methods and analysis: This protocol outlines the mixed methods strategy used for the development of the HEARTPA♀N content/core feature set (phase 2A), usability testing (phase 2B) and evaluation with a pilot randomised controlled trial (RCT) (phase 3). We are using the individual and family self-management theory, mobile device functionality and pervasive information architecture of mHealth interventions, and following a sequential phased approach recommended by the Medical Research Council to develop HEARTPA♀N. The phase 3 pilot RCT will enable us to refine the prototype, inform the methodology and calculate the sample size for a larger multisite RCT (phase 4, future work). Patient partners have been actively involved in setting the HEARTPA♀N research agenda, including defining patient-reported outcome measures for the pilot RCT: pain and health-related quality of life (HRQoL). As such, the guidelines for Inclusion of Patient-Reported Outcomes in Clinical Trial Protocols (SPIRIT-PRO) are used to report the protocol for the pilot RCT (phase 3). Quantitative data (eg, demographic and clinical information) will be summarised using descriptive statistics (phases 2AB and 3) and a content analysis will be used to identify themes (phase 2AB). A process evaluation will be used to assess the feasibility of the implementation of the intervention and a preliminary efficacy evaluation will be undertaken focusing on the outcomes of pain and HRQoL (phase 3). Ethics and dissemination: Ethics approval was obtained from the University of Toronto (36415; 26 November 2018). We will disseminate knowledge of HEARTPA♀N through publication, conference presentation and national public forums (Café Scientifique), and through fact sheets, tweets and webinars. Trial registration number: NCT03800082 .